2015
DOI: 10.5958/0974-9357.2015.00037.9
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Tracheal Suctioning Technique among Health Care Professionals: Literature Review

Abstract: a b s t r a c tThe work presents a comparative study of the effects of divalent (Pb), trivalent (La) and tetravalent (Ti) substituents on the multiferroic properties of BiFeO 3 (BFO). Both A and B-sites were substituted to obtain the compositions i.e. (Bi 1ÀxÀy La x Pb y )(Fe 1Àz Ti z )O 3 (x, y = 0, 0.1, 0.2 and z = 0, 0.05, 0.1, 0.15). Each of the substituent was particularly chosen i.e. Pb was chosen to keep the lone pair character which is the similar case as Bi ion. Additionally isovalent La was chosen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Nurses working in Khartoum teaching hospital Sudan had a better practice level than knowledge. A on the nurses knowledge regarding the phases of pre, during and post tracheal suctioning practices and its complications in Aga Khan University, Karachi Pakistan, concluded that the evidence based practices guidelines were followed and maintained by the health care professionals and play a vital role in enhancing safety of the patient [9]. Nurses showed appropriate practice patterns such as suctioning patients' mouths, oral care practices, and maintaining the appropriate pressure in the cuff of the endotracheal tube at a set level need to be evaluated to prevent the patient from VAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses working in Khartoum teaching hospital Sudan had a better practice level than knowledge. A on the nurses knowledge regarding the phases of pre, during and post tracheal suctioning practices and its complications in Aga Khan University, Karachi Pakistan, concluded that the evidence based practices guidelines were followed and maintained by the health care professionals and play a vital role in enhancing safety of the patient [9]. Nurses showed appropriate practice patterns such as suctioning patients' mouths, oral care practices, and maintaining the appropriate pressure in the cuff of the endotracheal tube at a set level need to be evaluated to prevent the patient from VAP.…”
Section: Discussionmentioning
confidence: 99%
“…While 20% of nursing students had inadequate knowledge and 80% had moderate knowledge [8]. A study [9] at Aga Khan University, Karachi Pakistan addressed the nurse's knowledge regarding the phases of pre, during and post tracheal suctioning practices and its complications concluded that the evidence based practices guidelines were followed by the health care professionals [9]. The current study helps to identify risks related to suctioning among patient in different hospitals of KPK.…”
Section: Introductionmentioning
confidence: 96%
“…Employing literature review as the methodology, multiple databases were searched focusing on three phases of tracheal suctioning (a) the pre suctioning phase, (b) the suctioning phase, (c) the post suctioning phase and complications related to tracheal suctioning. The study concluded that to provide quality care, it is important that the evidence based practice guidelines should be followed strictly [29].…”
Section: Literature Related To Practice Regarding Endotracheal Suctio...mentioning
confidence: 99%
“…which can be used for protecting and maintaining the airway, facilitating the artificial ventilation and removal of secretions from the lungs. 4 Hence, there was a need felt by the researcher to review the existing practices and knowledge of nurses related to ETS practices and thus recommending guidelines related to effective and safe practice. These guidelines and focused practice-based education would further have a positive impact on improving patient's outcomes, reduce healthcare costs, and promote safe patient care.…”
Section: Introductionmentioning
confidence: 99%